The Heidelberg Catechism on human sin and misery - R. S. Baard (Acta Theologica)
The Heidelberg Catechism’s section on Sin and Misery does not provide a moralistic or legalistic perspective on the human condition. Instead, it offers, in abbreviated format, a restatement of the doctrine of original sin, which points to sin as a condition and not just an act. As such, it invites us to think more deeply about the complexities of the human condition and of human agency.